In vitro interaction of Stenotrophomonas maltophilia with human monocyte-derived dendritic cells - Roscetto, Emanuela; Vitiello, Laura; Muoio, Rosa; Soriano, Amata A.; Iula, Vita D.; Vollaro, Antonio; Gregorio, Eliana De; Catania, Maria R. (Frontiers in Microbiology, 2015)
Stenotrophomonas maltophilia is increasingly identified as an opportunistic pathogen in immunocompromised, cancer and cystic fibrosis (CF) patients. Knowledge on innate immune responses to S. maltophilia and its potential modulation is poor. The present work investigated the ability of 12 clinical S. maltophilia strains (5 from CF patients, 7 from non-CF patients) and one environmental strain to survive inside human monocyte-derived dendritic cells (DCs). The effects of the bacteria on maturation of and cytokine secretion by DCs were also measured. S. maltophilia strains presented a high degree of heterogeneity in internalization and intracellular replication efficiencies as well as in the ability of S. maltophilia to interfere with normal DCs maturation. By contrast, all S. maltophilia strains were able to activate DCs, as measured by increase in the expression of surface maturation markers and proinflammatory cytokines secretion.